Molecular diversity of HIV-1 among people who inject drugs in Kuala Lumpur, Malaysia: massive expansion of circulating recombinant form (CRF) 33_01B and emergence of multiple unique recombinant clusters. - Wei Zhen Chow; Lai Yee Ong; Siti Humaira Razak; Yeat Mei Lee; Kim Tien Ng; Yean Kong Yong; Azureen Azmel; Yutaka Takebe; Haider Abdulrazzaq Abed Al-Darraji; Adeeba Kamarulzaman; Kok Keng Tee (PLoS ONE, 2013)
Since the discovery of HIV-1 circulating recombinant form (CRF) 33_01B in Malaysia in the early 2000 s, continuous genetic diversification and active recombination involving CRF33_01B and other circulating genotypes in the region including CRF01_AE and subtype B' of Thai origin, have led to the emergence of novel CRFs and unique recombinant forms. The history and magnitude of CRF33_01B transmission among various risk groups including people who inject drugs (PWID) however have not been investigated despite the high epidemiological impact of CRF33_01B in the region. We update the most recent molecular epidemiology of HIV-1 among PWIDs recruited in Malaysia between 2010 and 2011 by population sequencing and phylogenetic analysis of 128 gag-pol sequences. HIV-1 CRF33_01B was circulating among 71% of PWIDs whilst a lower prevalence of other previously dominant HIV-1 genotypes [subtype B' (11%) and CRF01_AE (5%)] and CRF01_AE/B' unique recombinants (13%) were detected, indicating a significant shift in genotype replacement in this population. Three clusters of CRF01_AE/B' recombinants displaying divergent yet phylogenetically-related mosaic genomes to CRF33_01B were identified and characterized, suggestive of an abrupt emergence of multiple novel CRF clades. Using rigorous maximum likelihood approach and the Bayesian Markov chain Monte Carlo (MCMC) sampling of CRF33_01Bpol sequences to elucidate the past population dynamics, we found that the founder lineages of CRF33_01B were likely to have first emerged among PWIDs in the early 1990 s before spreading exponentially to various high and low-risk populations (including children who acquired infections from their mothers) and later on became endemic around the early 2000 s. Taken together, our findings provide notable genetic evidence indicating the widespread expansion of CRF33_01B among PWIDs and into the general population. The emergence of numerous previously unknown recombinant clades highlights the escalating genetic complexity of HIV-1 in the Southeast Asian region.